Vulnerability and Chronic Illness Management in Pediatric Kidney and Liver Transplant Recipients. (June 2015) - Mavis, Alisha M.; Ertl, Allison; Chapman, Shelley; Cassidy, Laura D.; Lerret, Stacee M.
Context—: Solid-organ transplant is the treatment of choice for end-stage organ failure and requires a transition from management of a life-threatening condition to a chronic illness. Despite research focusing on quality of life after transplant, there is a gap addressing the role of managing a chronic illness focusing on vulnerability and impact on family. Objective—: Identify patient and family patterns of adaptation among kidney and liver transplant recipients in regard to (1) vulnerability, (2) impact of illness on the family, (3) family functioning, and (4) quality of life (parent and child report). Design—: Cross-sectional study enrolling children 5 to 18 years old and their parent at a single time point after kidney or liver transplant. Validated self-report tools were completed. Results—: In all, 47 participants (24 kidney and 23 liver) were recruited. Mean age at transplant was 4.0 (kidney) and 2.1 (liver) years. Mean age at report was 12.1 (kidney) and 7.1 (liver) years. Child vulnerability correlated negatively with (1) family impact in the kidney ( P < .05) and liver ( P < .05) transplant groups, (2) PedsQL subscales including Parent Emotional ( P < .05), Parent Social ( P < .01), Parent Psychosocial ( P < .01), Parent Physical ( P < .05), Parent School ( P < .05), and Child Social ( P < .01) in the kidney transplant group, (3) PedsQL Parent Emotional subscale ( P < .01) in the liver transplant group, and (4) Functional status ( P < .01) in the liver transplant group. Conclusions—: Child vulnerability provides insight into quality of life and the impact of illness on the family and family functioning.